2012
DOI: 10.1016/j.devcel.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The Sphingosine-1-Phosphate Receptor S1PR1 Restricts Sprouting Angiogenesis by Regulating the Interplay between VE-Cadherin and VEGFR2

Abstract: In the originally published version of this article, author Bà rbara Laviñ a was mistakenly listed as ''Bà rbara Laviñ a Siemsen.'' This error has now been corrected in the article online. We apologize for the error and any inconvenience that may have resulted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(101 citation statements)
references
References 0 publications
10
91
0
Order By: Relevance
“…Previous work has established that VE-cadherin, a main component of endothelial adherens junctions, is essential for angiogenesis and, in particular, the suppression of EC sprouting and proliferation 24,25 . We found that VE-cadherin distribution was substantially altered in Itgb1 iECKO retinal vessels (Fig.…”
Section: Inducible Inactivation Of Itgb1 In the Postnatal Endotheliummentioning
confidence: 99%
“…Previous work has established that VE-cadherin, a main component of endothelial adherens junctions, is essential for angiogenesis and, in particular, the suppression of EC sprouting and proliferation 24,25 . We found that VE-cadherin distribution was substantially altered in Itgb1 iECKO retinal vessels (Fig.…”
Section: Inducible Inactivation Of Itgb1 In the Postnatal Endotheliummentioning
confidence: 99%
“…Under these conditions, HLMVECs did not migrate against the flow direction over the course of 20 h, with many of the cells showing no directional preference (figure 4a,c; electronic supplementary material, figure S4). We next performed the same experiment, but supplemented media prepared with charcoal-stripped FBS and 100 nM of S1P, a physiologically relevant concentration [24,26,38] ( figure 4b,c). Under this condition, HLMVECs migrated against the flow direction with near identical radial migration distances and persistence to those of control, untreated, HLMVECs (figure 4d and electronic supplementary material,…”
Section: S1pr1 Is Required For Persistent Directional Migration In Rmentioning
confidence: 99%
“…In this model, S1PR1 may not be mechanically activated by flow, but is required to activate downstream signalling involved in flow-mediated collective migration. Given the known requirement of S1PR1 activity in proper VE-Cadherin localization in the developing microvasculature [24], it is possible that signalling via S1PR1 influences the assembly of the flow sensing complex consisting of PECAM, VE-Cadherin and VEGFR2/3 [10,17,21,55], and hence indirectly regulates flow sensing via this pathway.…”
Section: Cs-l15mentioning
confidence: 99%
See 2 more Smart Citations